The Implementation of Learning Organization in order to Increase Supply Chain Performance in SPR Maju Bersama Bojonegoro - Khairul Ikhwan; Anggraini Sukmawati; Eko Ruddy Cahyadi (Jurnal Manajemen & Agribisnis, 2018)
Sekolah Peternakan Rakyat (SPR) Maju Bersama was formed 3 years ago. SPR Maju Bersama still has some weaknesses in terms of human resource and supply chain performance. Learning organizations are needed for organizations to form an organization that can continuously run independent learning process, so that it has a fast thinking and acting to respond any changes. Therefore, SPR has to implement the learning organization. This paper aims to identify the effect of learning organization on supply chain performance in SPR Maju Bersama. A Model was developed and tested with quantitative and qualitative analysis. A total of 99 members of Sekolah Peternakan Rakyat Maju Bersama were used as data in this study. Quantitative data were analyzed using Structural Equation Mode- Partial Least Square (SEM-PLS). The results showed that learning organization had a positive impact on supply chain performance but not significant. Supply chain driver had a positive and significant impact on supply chain performance. Supply chain driver was significantly impacted by learning organization. Leadership style had a positive and significant impact on learning organization. SPR Maju Bersama needs to optimize its facility and information utility as a strategy to improve its supply chain performance.